THE NATURE OF PROPHAGE IN LYSOGENIC BACILLUS MEGATHERIUM - Miller, Elizabeth M. (The Rockefeller University Press, 1954)
1. By complement-fixation tests it has been shown that the lysogenic and sensitive strains of B. megatherium share one or more antigenic components which are serologically related but not identical. 2. Bacilli of the lysogenic strain of B. megatherium, when grown under conditions such that little extracellular phage is produced, fail to evoke antibodies in rabbits which react either in complement-fixation or neutralization tests with purified megatherium T phage. From this it must be concluded either that prophage is not antigenic or that any antibody which it might elicit does not react with the antigens of the mature virus. The observations reported in this communication accord with the hypothesis that prophage is a genetic structure.